Faulkner and the Ecology of the South - Abadie, Ann J.; Urgo, Joseph R. (Book collections on Project MUSE., 2005)
In 1952, Faulkner noted the exceptional nature of the South when he characterized it as "the only really authentic region in the United States, because a deep indestructible bond still exists between man and his environment.". The essays collected in Faulkner and the Ecology of the South explore Faulkner's environmental imagination, seeking what Ann Fisher-Wirth calls the "ecological counter-melody" of his texts. "Ecology" was not a term in common use outside the sciences in Faulkner's time. However, the word "environment" seems to have held deep meaning